Partial resistance of soybean lines to asian rust and white mold (Bioscience Journal, 2018)
Soybean Asian rust and white mold stand out to cause great problems to soybean producing regions in Brazil. The aim of this study was to evaluate the partial resistance of soybean lines to Asian rust and white mold. In order to assess the resistance of soybean to Asian rust, 19 early maturing soybean lines were used in an experiment in a greenhouse. Four severity evaluation were carried and the area under the disease progress curve was calculated. The productivity of those lines was evaluated in the field. In a second experiment, the resistance to Sclerotinia sclerotiorum was assessed under greenhouse conditions. When the plants were in the V2 stage, the inoculation was carried by cutting the main stem and inserting a ferrule containing the fungal mycelium. Seventeen soybean lines and the controls Emgopa 316 and Nidera RR 7255 were evaluated. The averages were grouped by the Scott Knott test by using the software Assistat. The lines L203 and L279 showed partial resistance to Phakopsora pachyrhizi and good productivity. The inoculation method was efficient in assessing the resistance to S. sclerotiorum. The lines L203, L268, L266, L226, L144 and L267 were resistant to the infection of S. sclerotiorum.